2023
DOI: 10.1111/jipb.13453
|View full text |Cite
|
Sign up to set email alerts
|

PagERF81 regulates lignin biosynthesis and xylem cell differentiation in poplar

Abstract: Lignin is a major component of plant cell walls and is essential for plant growth and development. Lignin biosynthesis is controlled by a hierarchical regulatory network involving multiple transcription factors. In this study, we showed that the gene encoding an APETALA 2/ethylene-responsive element binding factor (AP2/ERF) transcription factor, PagERF81, from poplar 84 K (Populus alba × P. glandulosa) is highly expressed in expanding secondary xylem cells. Two independent homozygous Pagerf81 mutant lines crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Lignin biosynthesis has been studied intensively in recent decades and many studies reported that the TF-regulated lignin biosynthesis pathways were correlated with stress resistance in plants [ 35 ]. Previous studies showed that AP2/ERF family members could regulate the lignin biosynthesis genes in response to stress [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the current study, RNA-Seq data indicated that the phenylpropanoid biosynthesis pathway was enriched in overexpression- ScDREB10 plants under osmotic stress, which is in accordance with the high-lignin-biosynthesis-related gene expression level in OE plants under osmotic stress ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lignin biosynthesis has been studied intensively in recent decades and many studies reported that the TF-regulated lignin biosynthesis pathways were correlated with stress resistance in plants [ 35 ]. Previous studies showed that AP2/ERF family members could regulate the lignin biosynthesis genes in response to stress [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the current study, RNA-Seq data indicated that the phenylpropanoid biosynthesis pathway was enriched in overexpression- ScDREB10 plants under osmotic stress, which is in accordance with the high-lignin-biosynthesis-related gene expression level in OE plants under osmotic stress ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…pyramidalis [9], etc. On this basis, the mechanisms of functional genes involved in various biological processes of poplar have also been studied, such as growth and development [10,11], stress response [12,13], wood formation [14][15][16], and sexual differentiation. However, as a woody plant, poplar has some unique features in terms of life cycle, morphological structure, and environmental adaptability [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the well‐established correlation between vessel traits and hydraulic conductance, the precise mechanisms by which trees coordinate vessel development in response to drought remain incompletely understood. Notably, transgenic poplars overexpressing PtrERF139 , PtaERF194 , and PagERF81 have shown altered vessel characteristics, including reduced vessel size, increased vessel frequency, and enhanced lignin deposition (Wessels et al ., 2019; Wang et al ., 2022; X. W. Zhao et al ., 2023). These findings suggest the potential involvement of ERF transcription factors in regulating adaptive vessel development in response to drought in Populus .…”
Section: Introductionmentioning
confidence: 99%